DETERMINAN KEJADIAN ANEMIA PADA REMAJA PUTRI - Palaguna, Sriwati; Rauf, Darmawaty; Putra, Bayu Pratama (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Anemia is one of the public health problems that is still commonly found in Indonesia and affects various age groups. The purpose of this study was to determine the determinants of anemia in adolescent girls. A cross-sectional study design was used in this study. The study was conducted in several junior high schools in Barito Putra Regency. The study was conducted in January 2025. The population consisted of female students from several junior high schools in Barito Putra District. The sample size was 70 participants. The sampling technique used was purposive sampling. The research instrument was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between dietary patterns (p-value: 0.00) and parental income (p-value: 0.00) with the incidence of anemia among adolescent girls. It is recommended that the adolescent girls in this study take preventive measures against anemia by improving their dietary patterns and selecting a variety of food types. Keywords: Diet, Income, Teenagers.